Advanced Data Framework for Sleep Medicine Applications: Machine Learning-Based Detection of Sleep Apnea Events - Kristina Zovko; Yann Sadowski; Toni Perković; Petar Šolić; Ivana Pavlinac Dodig; Renata Pecotić; Zoran Đogaš (Applied Sciences)
Obstructive Sleep Apnea (OSA) is a prevalent condition that disrupts sleep quality and contributes to significant health risks, necessitating accurate and efficient diagnostic methods. This study introduces a machine learning-based framework aimed at detecting apnea events through analysis of polysomnographic (PSG) and oximetry data. The core component is a Long Short-Term Memory (LSTM) network, which is particularly suited to processing sequential time-series data, capturing complex temporal relationships within physiological signals such as oxygen saturation, heart rate, and airflow. Through extensive feature engineering and preprocessing, the framework optimizes data representation by normalizing, scaling, and encoding input features to enhance computational efficiency and model performance. Key results demonstrate the model’s effectiveness, achieving a balanced accuracy of 79%, precision of 68%, and recall of 76% on the test dataset, with validation set metrics similarly high, supporting the model’s ability to generalize effectively. Comprehensive hyperparameter tuning further contributed to a stable, robust architecture capable of accurately identifying apnea events, providing clinicians with a valuable tool for the early detection and tailored management of OSA. This data-driven framework offers an efficient, reliable solution for OSA diagnostics with the potential to improve clinical decision making and patient outcomes.